TINJAUAN HUKUM PERDA SYARIAH KOTA TASIKMALAYA NOMOR 7 TAHUN 2014 DALAM PRESPEKTIF HUKUM TATA NEGARA - nurjamal, ecep (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
The Regional Autonomy Policy (Otda) in the post-New Order era has brought about major changes in the political system in Indonesia, which was originally centralized to become decentralized. The purpose of this study is to determine the position of PERDA in the post-reform Indonesian legal system. The approach to be used is an empirical juridical approach. The research is based on an inventory of positive law, the discovery of legal principles and the discovery of inconcretto law, complemented by empirical observations of the operationalization of law in society. The results of this study show that the Sharia regional regulations that have been widely enforced in the regions to date, are recognized as having benefits, including increasing public security and order. What is also important to study, is that the increased sense of security in society needs to be examined and further investigated, because this symptom may just be an effect or a reflection of the public's fear of sharia. If so, then this phenomenon is not a true reflection of the strengthening of legal and security institutions. That is, what actually takes place is not citizen legal compliance as a result of the objective situation that is created, but because of a perceived fear of the sharia police who are perceived as carrying out their duties in the name of religion